New species of Evaniodini (Braconidae: Doryctinae) from Brazil - Valerio, Alejandro A (Zootaxa, 2016)
A new species, Evaniodes costatus Valerio sp. nov., belonging to the tribe Evanoidini is described and illustrated. The new species is compared with the five species currently known to occur in the genus Evaniodes Szépligeti.